Torsional strain inversed chemoselectivity in a Pd-catalyzed atroposelective carbonylation reaction of dibenzothiophenium. Issue 13 (9th March 2022) - Zhang, Qiuchi; Xue, Xiaoping; Hong, Biqiong; Gu, Zhenhua
Abstract : Torsional strain inversed chemoselectivity: from bond a to bond b. Abstract : A palladium-catalyzed enantioselective ring-opening/carbonylation of cyclic diarylsulfonium salts is reported. In comparison to thioethers, the sulfonium salts displayed high reactivity and enabled the reaction to be performed under mild conditions (room temperature). The steric repulsion of the two non-hydrogen substituents adjacent to the axis led cyclic diarylsulfonium salts to be distorted, which enabled the ring-opening reaction to proceed with significant preference for breaking the exocyclic C–S bond.